KUALITAS GIZI DAN KECERNAAN BAHAN ORGANIK SECARA IN VITRO HAY RUMPUT UNTUK SAPI ANTAR PULAU DI STASIUN KARANTINA TENAU KUPANG - L.J.M. Christna Kale Lado; Aholiab Aoetpah (Politeknik Pertanian Negeri Kupang, 2009)
A study was conducted to evaluate nutrient composition and in-vitro digestibility of organic matter of native grass hay usually used to feed Bali cattle in the Quarantine of Tenau Kupang and cattle during shipping. Method use were sampling the hay grass from five piles of grasses, identifying the species, analyzing nutrient composition and examining in-vitro digestibility of organic matter. Results of the study showed that the dominant hay grasses in Quarantine were native grass and kume grass (Sorghum plumosum var. timorense). Nutrient content of the native grass are dry matter (92.21%), ash (3.85%) and crude protein (5.01%). These numbers are higher than numbers in kume grass but organic matter and neutral detergent fiber. The in-vitro digestibility of organic matter was higher in native grass (48.01%) than that in kume grass (40.81%). It was concluded that hay grass used to feed cattle in the Quarantine and cattle during shipping are dominated by native grass and kume grass. Nutrient composition especially dry matter, ash and crude protein in native grass are higher than numbers in kume grass but organic matter and neutral detergent fiber. Consequently, in-vitro digestibility of native grass is higher than that in kume grass.Key words: nutrient, in-vitro digestibility, hay grass, quarantine, shipping